The value of a party: local politics and the allocation of intergovernmental transfers - Quinckhardt, Matthias (European journal of political economy, 2023)
This paper investigates how party connections affect the ability of local politicians to obtain central government funds for their municipality. Using a novel data set for mayoral elections in Germany spanning 2322 municipalities in eight states in the years 2000 to 2008 and regression discontinuity design, I find that party alignment between a local mayor and the state government increases transfers to a municipality by 20% per year. Such favoritism has been interpreted as a sign of partisanship and blamed on central governments which use public funds for partisan purposes. I show that local political conditions, such as reelection incentives and information transmission can partly account for the alignment effect. Taken together, the results provide alternative channels for the interpretation of alignment effects.
Gesehen am 12.03.2024